Kontribusi Kiai Kholil Bangkalan dalam Mengembangkan Tasawuf Nusantara - Mohammad Takdir (Institut Ilmu Keislaman Annuqayah, 2016)
This paper aims to elaborate the sufism thought of Kiai Kholil as Madurese scholars who still remembered and respected until now. He has important role in spreading Islam with sufism approach and also has been successfully shaping the best muslim generations. This study uses library research to reveal the thought and the role of Kiai Kholil in developing sufism in the Nusantara. This study uses descriptive method to gain a comprehension of his figure known as sufi that inspire muslim generations in Nusantara. The results of this study show that Kiai Kholil has a big contribution in the development of Sufism in Nusantara. The First, Kiai Kholil developed tarekat in Madura, because he has become member of Qadariyah wa Naqsabandiyah Tarekat. Kiai Kholil manages to practice sufism harmoniously to the norms of fiqh. Based on the norms of fiqih, sufism was successfully accepted by people. The second, Kiai Kholil successfully developed the thought and practice of sufism based on the character of ahlussunah wa al-jama>’ah. In this way, he integrates sufism into the life of the society. The character of sufism developed by Kiai Kholil based on ahlussunah wa al-jama>’ah were accepted by the majority of Indonesian society, which emphasize on mutual respect (tasa>muh), balance (tawa>zun), justice (taa>dul) and moderation (tawa>sut).